IMPLEMENTASI PENGENALAN WAJAH BERBASIS CNN DAN RFID UNTUK AREA AKSES AMAN DI FASILITAS POLSRI DENGAN HOSTING LOKAL - Permata Sari, Dewi; Arya Cendekia Putra, Muhammad; RD.Kusumanto (JURNAL TELISKA, 2024)
This research is designed to optimize the process of accessing sterile or high-security areas by integrating RFID and CNN technologies to minimize manual intervention. RFID can quickly, accurately, and automatically identify each individual, while the CNN algorithm for facial recognition ensures more accurate and secure authentication. The combination of these two technologies creates an innovative solution to address various challenges present in conventional systems. Additionally, the use of a website with a local server allows for real-time monitoring and management of data, providing ease in data processing and analysis in these areas